Effects of periparturient anthelmintic treatment on milk yield and quality in dairy cows - Borman, Adil; Islam, Md Faruk; Rahman, Md Shajedur; Hoque, Md Fazlul; Kispotta, Sandip; Haque, Md Anowarul (Asian Journal of Medical and Biological Research, 2016)
This study was conducted to determine the efficacy of anthelmintics against gastrointestinal parasite in periparturient dairy cows and its effect on milk yield and quality. Sixty mixed breed pregnant cows were selected divided into four groups, A (n=18), B (n=14), C (n=16) and D (n=12) and group D kept as control. Cows of group A were treated with Nitroxynilat the rate of 10 mg/kg bwt. s/c, 30 days before parturition and average feacal egg per gram(EPG) was reduced from 506.1 ± 172.3 to 157.8 ± 24.9 within 14 days. Group B were treated with combined triclabendazole and levamisoleat the rate of19.5 mg/kg bwt. orally at calving. The average EPG was reduced from 967.7 ± 237.1 to 172.0 ± 25.9. Group C were treated with same as group B at calving and 42 days after. The mean EPG fall from 794.6 ± 310.5 to 166.7 ± 26.2.In group D average EPG increased from 791.7 ± 268.5 to 864.2 ± 290.7. The mean change in EPG 14 days after treatment was significantly higher (p<0.05) in treated (79.1%) cows than control (-9.2%). The average milk yield in all treated cows was significantly (p<0.01) higher in treated lactation (2.5 ± 0.7) than previous lactation (2.2 ± 0.7) and control cows (2.2 ± 0.8). Although, milk yields were higher in second parity (2.5 ± 0.7) than the first (2.4 ± 0.7), there was no significant difference (p>0.05). The percentage of milk fat, protein, lactose, SNF was significantly higher (P<0.05) in treated group than the control group. Asian J. Med. Biol. Res. September 2016, 2(3): 409-413